Fostering 21st Century Skills Through Product-Based Learning with a Focus on Collaboration in Higher Education - Andrianto, Rico Eko; Khotimah, Khusnul; Laksana, Ilham; Maulana, Iwan; Amarulloh, Adhitya; Rabbani, Arsyananda; Djatmiko (Journal of Education Reseach and Evaluation, 2025)
Universities are no longer sufficient to emphasize only cognitive aspects. However, they must also be able to facilitate students in developing practical skills relevant to the needs of the workplace and society. This study aims to analyze the effect of Product-Based Learning (PBL) on the collaboration skills of vocational students in the Visual Communication Design (VCD) program. The method was a quasi-experimental posttest-only control group design with a sample of 72 students, divided into experimental (PdBL) and control (Project-Based Learning) groups. The instruments were questionnaires and observations of six aspects of collaboration skills. Data analysis used a t-test and Cohen's d effect size calculation. The results showed that implementing product-based learning significantly improved students' collaboration skills, reflected in their ability to work in teams, share roles, and constructively resolve conflicts. Students also showed positive developments in 21st-century skills, such as effective communication, creative problem-solving, and critical thinking skills in designing and producing products relevant to real needs. The effect size confirms that PdBL has a very strong impact on improving collaboration skills. The novelty of this research lies in the quantitative analysis of the effect size of PdBL in vocational education in Visual Communication Design (DKV), a practice rarely studied before. The implication is that PdBL can be an effective strategy for strengthening 21st-century soft skills, particularly collaboration, while also addressing the needs of the creative industry and Society 5.